The role of entrepreneurship education and family environment on entrepreneurial interest students through student entrepreneurship motivation at private universities in Serang city - Afiah, Efi Tajuroh; Nurizki, Aris Trismayadi; Saputra, Saripudin; Permata, Nuniek (International Journal of Applied Finance and Business Studies, 2025)
This study aims to analyze the influence of entrepreneurship education and family environment on students' interest in entrepreneurship, with entrepreneurial motivation as a mediating variable. The study was conducted on 150 students from several private universities in Serang City who had taken entrepreneurship courses. The method used was a quantitative approach with Structural Equation Modeling (SEM) analysis using SmartPLS software. The results showed that entrepreneurship education and family environment positively and significantly influence entrepreneurial motivation. Additionally, entrepreneurial motivation significantly influences students' interest in entrepreneurship. Motivation was also found to significantly mediate the relationship between entrepreneurship education and family environment on entrepreneurial interest. The theoretical contribution of this study is to strengthen motivation theory and planned behavior theory in the context of entrepreneurship among students. The practical contribution is that this study provides recommendations to higher education institutions to strengthen practice-based entrepreneurship curricula and encourage family involvement in shaping students' entrepreneurial mindset and spirit.